The Doha trade round and Mozambique - Arndt, Channing (Policy research working paper, 2005)
"This paper considers the potential implications of the Doha Development Agenda, as well as other trade liberalization scenarios, for Mozambique. An applied general equilibrium model, which accounts for high marketing margins and home consumption in the Mozambique economy, is linked to results from the GTAP model of global trade. In addition, a microsimulation module is used to consider the subsequent implications of trade liberalization for poverty. The implications of trade liberalization, particularly the Doha scenarios, are found to be relatively small. Presuming that a more liberal trading regime will positively influence growth in Mozambique, an opportunity exists to put in place such a regime without imposing significant adjustment costs. "--World Bank web site